Analisis Komunikasi Pemasaran E-Commerce pada Brecht Indonesia - Ibanez Vienoza Ngan; Wulan Purnama Sari (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2022)
The development of marketing communication today is not only done conventionally. Marketers are now also using new media such as the Internet as an alternative to approach potential customers. In carrying out marketing communications, companies must know what the needs of consumers are. The title of this research is